SCREENING FOR MULTIDRUG RESISTANCE BACTERIA PSEUDOMONAS AERUGINOSA IN HOSPITALIZED PATIENT IN HOSUR, KRISHNAGIRI (DT) - S.PARANJOTHI,; R.DHEEPA, (International Journal of Pharma and Bio Sciences, 2010)
Pseudomonas aeruginosa is a classic opportunistic pathogen because of its innate resistance to many antibiotics and disinfectants. It is also the most common Gram negative bacterium found in nosocomial infections causing various spectra of infections especially in neutropenic, immunocompromised, burns / tissue injury and cystic fibrosis patients all over the world. Recent advances in medicine such as the advent of more elaborate surgery and intensive care, the use of immunosuppressive drugs, the availability of invasive procedures and the increase in number of immunocompromised patients means there is a rise in patients with impaired immune defences liable to nosocomial infections. The increasing incidence of infections caused by multidrug resistant organisms have caused attention to be focused on measures for fighting resistance, foremost of which is susceptibility surveillance .This study therefore determined the prevalence, antibiotic susceptibility and resistant patterns of Pseudomonas aeruginosa strains from clinical specimens.